Is Radiotherapy Useful for Treating Pain in Mesothelioma?. Issue 6 (June 2015) - MacLeod, Nicholas; Chalmers, Anthony; O'Rourke, Noelle; Moore, Karen; Sheridan, Jonathan; McMahon, Lynn; Bray, Caroline; Stobo, Jon; Price, Alan; Fallon, Marie; Laird, Barry J.
<x xml:space="preserve">Abstract</x> Introduction: Radiotherapy is often used to treat pain in malignant pleural mesothelioma (MPM), although there is limited evidence to support this. The aim of this trial was to assess the role of radiotherapy for the treatment of pain in MPM. Methods: A multicentre, single arm phase II trial was conducted. Eligible patients fulfilled the following criteria: pathological or radiological diagnosis of MPM; pain secondary to MPM; radiotherapy indicated for pain control; and more than 18 years of age. Patients had assessments of pain and other symptoms at baseline and then received 20 Gy in five daily fractions. Key follow-up points were 5 and 12 weeks posttreatment. The primary end point measure was assessment of pain at the site of radiotherapy at 5 weeks. Secondary end points included effects on quality of life, breathlessness, fatigue, mood, toxicity, and the radiological response. Results: Forty patients were recruited from three UK oncology centers. Fourteen patients had a clinically meaningful improvement in their pain 5 weeks post radiotherapy (intention to treat), with five patients having a complete improvement. On the basis of a complete case analysis of the 30 patients assessable at week 5, 47% (confidence intervals, 28.3–65.7) of patients alive at week 5 had an improvement in their pain. There was no improvement in other key symptoms or quality of life. Conclusions: Radiotherapy for pain control in MPM is an effective treatment in a proportion of patients. Future studies examining differing radiotherapy regimens with a view to improving response rates are warranted.